Σχεδιασμός τροχοκαθίσματος για μετακίνηση σε κλιμακοστάσια - Κυριακίδης, Δημήτρης; Χατζημάρκου, Ειρηναίος; Βουτουρής, Φώτης (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
People with disabilities experience daily discriminations at all levels of life, influencing negatively their psychological and physical situation. It is globally known that the infrastructures, services and goods are not properly designed to facilitate their accessibility. This causes a sense of marginalization and exclusion from the society. Therefore, in order to resolve this problem, a study on the design of various mechanisms that would correspond in the needs of accessibility in places containing stairs, thus facilitating their daily movement, is highly required. The purpose of this study is to investigate mechanisms able to be attached to wheelchairs and furthermore help people with disabilities to partially relieve their movement when they are faced with an obstacle, such as stairs. The method used for the survey was the creation of a questionnaire that it could help us understand the problems faced by people with disabilities, with the ultimate goal of focusing the design on the points that need further improvement. Several stair climbing mechanisms in the market have been studied, as well as similar studies. The main goal of this study was the design of an innovative device which is not currently on the market and is characterized by its uniqueness as it aimed to be modular. Specifically, it can be attached to various types of wheelchairs after appropriate modifications to the existing one. The system has been designed so that the person is always in a forward position relative to the direction of movement of the device. In particular, the device consists of five linear actuators which will control the position of the wheelchair. These will change the center of gravity, to ensure the balance of the whole system. The movement (elevation) of the system is controlled by sensors, a data acquisition/processing card and a joystick. The parts of the system have been sketched using the SolidWorks 2017 software. Τhe study of stress analysis has been calculated analytical and compared with the computational results received from the program. Also, dynamic simulation of the system was computed using Matlab code. After selecting the key components of the system through research on the global market and communicating with companies, for further modifications to meet the specifications set, we made the necessary orders. Upon receipt of all the components, the prototype was built to fully visualize the device at Thomason Machinery's high-tech machine shop. It is obvious that the assembly of a prototype will better evaluate its drawbacks and advantages, which can lead to future improvements and upgrades.
Keywords: Stair-climbing wheelchair; Electric wheelchair; Attachment; Limited mobility; Disabled people; Accessibility; Ανάβαση σε κλιμακοστάσια; Τροχοκάθισμα; Ηλεκτροκινούμενο τροχοκάθισμα; Προσάρτηση; Περιροσμένη κινιτηκότητα ΑμεΑ; Προσβασιμότητα